Effects of the Covid-19 pandemic on the oceans. Issue 4 (3rd April 2021) - Al Shehhi, Maryam R.; Abdul Samad, Yarjan
ABSTRACT: A lockdown due to the novel coronavirus (COVID-19) resulting in the closure of largest industries in the world for a period of 2 months was enough to cause a drop of 7% of the anthropogonic carbon dioxide (CO2 ) in the atmosphere. Besides, the atmosphere oceans play a key role to buffer the greenhouse effect. Herein, the resultant reduction in CO2  emissions on the productivity of the global oceans are studied. Often chlorophyll- a  (chl- a ), particulate inorganic and organic carbon (PIC:POC), and sea surface temperature (SST), are used to indicate the productivity of oceans. Based on the satellite estimates, a drop in chl- a  is observed in North Europe, South China and Southeast USA during the pandemic. The observed reduction in mean chl- a  by around 5% in China may have occurred due to a drop of 123 tonnes of CO2  emissions. A cooling response of 0.5°C in mean SST is observed over most of the coastal areas. A considerable drop in CO2 emissions in the North Indian Ocean translates into a drop of mean SST in the region by 5%. All these suggest that maintaining global activities as sustainable as the pandemic period, can help to recover the oceans.